OPTIMALISASI LITERASI MEDIA SOSIAL UMKM DESA NGRINGO, KECAMATAN JATEN, KABUPATEN KARANGANYAR - Dani, Jeratallah Aram Dani; Setiawan, Ali Arif; Pramuktisari, Nindita; Wijayanti, Christina Nur; Harjono, Harjono; Syaifullah, Jahid; Fardhila, Widityana Ayu; Poundra, Emmanuelle (Abdi Masya, 2025)
DIDU has become a new phenomenon among entrepreneurs, both small and large. One of them is the MSME world, which has evolved into a long-term program aimed at enhancing human resources and socio-economic conditions. Through the dynamics and development of technology, mass media have become an essential tool that meets primary needs, allowing the community to utilise them according to their needs and benefits. Therefore, literacy and optimisation are necessary for its effective operationalisation. This is important to convey through semi-formal activities from the academy to the community, as practitioners, by collaborating in the Ngringo Village MSME Expo event. With the aim of providing enrichment and updated and upgraded insights to optimise the use of social media as a business tool. Using a qualitative approach with surveys, observations, and face-to-face interviews, and ending with group discussions with business actors. Getting a discussion of the needs of academics and practitioners in improving business needs and producing interactive and innovative responses and discussions, one of which is providing a level of protection to prevent cases of fraud online. The advantages and disadvantages of organising Expo events are continually being improved to ensure consistency in building businesses on an MSME scale.